Gram‐scale separation of borneol and camphor from Cinnamomum camphora (L.) Presl by continuous counter‐current chromatography. Issue 2 (5th February 2018) - Yang, Zhi; Guo, Peipei; Han, Rui; Wu, Shihua; Gao, Jin‐Ming
Abstract: Borneol and camphor are well known bicyclic monoterpenoids and have been widely used in food, senior aromatic spices and folk medicine in China, India and Japan for more than 2000 years. Although they can be obtained by recrystallization or sublimation, it is still a challenge to prepare high‐purity borneol and camphor with high yields. In this study, we introduce a new continuous counter‐current chromatography method for the gram‐scale preparation of borneol and camphor from Cinnamomum camphora (L.) Presl using heptane/ethyl acetate/methanol/water quaternary solvent system and heptane/methanol/water ternary solvent system. Compared to the heptane/ethyl acetate/methanol/water solvent system, the heptane/methanol/water solvent system was found to possess higher loading capacity, and the heptane/methanol/water (10:7:3, v/v/v) solvent system was found to be the optimal solvent system for the separation of the distillation products of C. camphora . As a result, borneol and camphor were well obtained in a one‐step separation with a purity of over 99.9%. In addition, continuous injections method using "on demand" solvent system formulation was used to improve the separation efficiency and reduce solvent consumption, whose results indicated that counter‐current chromatography was a powerful and efficient tool to obtain borneol and camphor with high purity.